2015
DOI: 10.18257/raccefyn.192
|View full text |Cite
|
Sign up to set email alerts
|

Identificación genética de aislamientos de Colletotrichum spp. causantes de antracnosis en frutos de aguacate, banano, mango y tomate de árbol

Abstract: ResumenLa antracnosis es una de las enfermedades que más afecta la producción de frutales tropicales en el mundo. El objetivo del presente trabajo fue identificar a nivel de especie aislamientos de Colletotrichum spp. causantes de la antracnosis en frutos de aguacate, banano, mango y tomate de árbol mediante el análisis filogenético multilocus empleando datos de las secuencias de la región espaciadora interna transcrita (ITS), y de los genes β-tubulina-2 y gliceraldehído-3-fosfato deshidrogenasa. Para cada esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
0
7
0
3
Order By: Relevance
“…and peanut leaf spots (Arachis). In Brazil, the pathogen C. fructicola was also reported in mango by Viera et al [40] and also it has been reported in Asia, Africa, and America in various hosts as the cause of anthracnose [41]. Likewise, Fuentes-Aragón et al [37] confirmed that C. fructicola was previously reported as C. gloeosporioides and then it was reclassified.…”
Section: Morphological Identificationmentioning
confidence: 80%
“…and peanut leaf spots (Arachis). In Brazil, the pathogen C. fructicola was also reported in mango by Viera et al [40] and also it has been reported in Asia, Africa, and America in various hosts as the cause of anthracnose [41]. Likewise, Fuentes-Aragón et al [37] confirmed that C. fructicola was previously reported as C. gloeosporioides and then it was reclassified.…”
Section: Morphological Identificationmentioning
confidence: 80%
“…Further studies involving multilocus phylogenetic analysis based on sequencing data from the ITS region and from the βtubulin-2 and glyceraldehyde-3-phosphate dehydrogenase genes has identified Colletotrichum asianum, Colletotrichum fructicola, and Colletotrichum musae as members of the Colletotrichum gloeosporioides species complex, known to cause anthracnose in various fruit (Gañán et al, 2015). More so, Bayesian multilocus phylogenetic analyses performed using amplified sequences of the internal transcribed spacer region of the nuclear ribosomal DNA; actin, chitin synthase, glyceraldehyde-3-phosphate dehydrogenase partial genes; and APn2-Mat1-2 intergenic spacer and mating type Mat1-2 partial gene reported Colletotichum fruticola as one of the species that forms Colletotrichum gloeosporioides.…”
Section: The Pathogen: Colletotrichum Gloeosporioidesmentioning
confidence: 99%
“…These were then suspended at a concentration of 1.0 × 10 6 UFC/ml in sterile distilled water and identified according to the taxonomic keys published by Gañán, Álvarez and Castaño (2015); the identification was verified through molecular analyzes carried out in the laboratories of Corporación para Investigaciones Biológicas [Corporation for Biological Studies] (cib) in Medellin, with dna extractions using hexadecyltrimethylammonium bromide (ctab). Amplification in the internal transcribed spacer (its) region with a polymerase chain reaction (pcr) technique was carried out using universal primers and sequencing.…”
Section: Pathogen Isolation and Inoculum Productionmentioning
confidence: 99%
“…Bacteria, fungi and actinomycetes counts were carried out for each sample and expressed in colony forming units (cfu) per gram of soil, using the serial dilutions technique and draining in Petri dishes according to the methodology published by Tofiño et al (2012) and Gañán et al (2015). Likewise, soil quality indicators as pH, organic matter, cation exchange capacity (cec) and electric conductivity (ec) were measured.…”
Section: Physicochemical Biological and Yield Criteria Measurementsmentioning
confidence: 99%